213k views
1 vote
HELP HELP HELP HELP PLEASE

HELP HELP HELP HELP PLEASE-example-1
User Morsor
by
5.6k points

2 Answers

1 vote

Answer:

2

Explanation:

6^2 - 36 ÷ 3^2 x 4 -18

Using BODMAS -Brackets, Of, Division/Multiplication, Addition/Subtraction.

=36 -(36 ÷ 9) x 4 -18

=36 - 4 x 4 -18

=36 -16-18

=2

User Tengis
by
5.2k points
6 votes

Answer:

2

Explanation:

Following the order of operations as set out in PEMDAS

6² - 36 ÷ 3² × 4 - 18 ( no parenthesis so evaluate exponents )

= 36 - 36 ÷ 9 × 4 - 18 ( multiplication/ division, evaluate from left to right )

= 36 - 4 × 4 - 18

= 36 - 16 - 18

= 20 - 18

= 2

User Amresh
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.